Comparative Analysis of Twisted Vertical Axis Turbine Blades of Naca 4-Series- Experimental Approach - Shaik, Mubeen; Suresh, S; Kumar, Algot Kiran (International Journal of Psychosocial Rehabilitation, 2025)
Low velocity vertical axis wind turbines need to be analysed in both the ways, in that one is twisted angle and second one is wind velocity. The comparison of twisted blades of 4 series with geometrical deviations need to observe and the variations should be considered. Present study is a comparison of two NACA 4-series profiles NACA4412, NACA 4418 with twisted profiles to check the affect of twist on lift and drag parameters. Primary work with CFD in ANSYS workbench has been considered for the comparison with twisted angle deviation ranging from 5,10,15 degrees. The twisted profile investigated with aerodynamic environment with different velocities ranging from 5-8m/s. NACA 4412 given good results in CFD with at low speeds compare with NACA 4418. The approach further carried-out for the experiment to check the evaluation of twist angle and optimum velocity. The experimental work has been carried-out for the twist of 50 which is better in simulation and at an attacking angle of 150. The results obtained shows better enhancement nearly 14% when compare with straight blade without any twist.